Regulatory Compliance and Innovation: A Literature Analysis on the Impact of Sustainability Legislation on Engineering and Supply Chain Innovations by the Example of the German Circular Economy Act - Wanja Wellbrock; Asli Ercengiz; Daniela Ludin (Tehnički Glasnik)
This paper examines the effects of sustainability laws on innovation, with a particular focus on the German Circular Economy Act. The study investigates whether strict environmental regulations promote technological advances and sustainable business practices. The results show a differentiated picture. While the German Circular Economy Act and similar regulations encourage companies to adopt resource-efficient practices, the level of innovation varies significantly between industries. Industries such as packaging and high technology are showing remarkable progress, including the development of sustainable materials and optimized product designs for recycling and repair. In contrast, challenges such as high initial costs, technological complexity and regulatory uncertainties make it difficult to innovate, especially for small and medium-sized enterprises. In addition, supply chain innovations are often consistent with lean management principles, which shows how regulatory frameworks can contribute to leaner processes and a reduction in waste.